Salvianolic acid B combined with bone marrow mesenchymal stem cells piggybacked on HAMA hydrogel re-transplantation improves intervertebral disc degeneration - Hu, Jie; Li, Cai; Jin, Shichang; Ye, Yuchen; Fang, Yuekun; Xu, Panpan; Zhang, Changchun (Frontiers in Bioengineering and Biotechnology, 2022)
Cell-based tissue engineering approaches have emerged as a realistic alternative for regenerative disc tissue repair. The multidirectional differentiation potential of bone marrow mesenchymal stem cells (BMSCs) to treat disc degeneration (IDD) has also become a viable option. We used 1% HAMA hydrogel as a carrier and co-encapsulated BMSCs and Salvianolic acid B (SalB) into the hydrogel to reduce the apoptosis of the transplanted cells. The protective effect of SalB on BMSCs was first verified in vitro using the CCK8 method, flow cytometry, and Western-Blotting, and the physical properties and biocompatibility of HAMA hydrogels were verified in vitro. The rat model was then established using the pinprick method and taken at 4W and 8W, to examine the extent of disc degeneration by histology and immunohistochemistry, respectively. It was found that SalB could effectively reduce the apoptosis of BMSCs in vitro by activating the JAK2-STAT3 pathway. 1% HAMA hydrogels had larger pore size and better water retention, and the percentage of cell survival within the hydrogels was significantly higher after the addition of SalB to the HAMA hydrogels. In the in vivo setting, the HAMA+SalB+BMSCs group had a more pronounced delaying effect on the progression of disc degeneration compared to the other treatment groups. The method used in this study to encapsulate protective drugs with stem cells in a hydrogel for injection into the lesion has potential research value in the field of regenerative medicine.